Pengembangan Web Antrian Terapi RSUD Syarifah Ambami Rato Ebu Menggunakan Waterfall dan SUS - Rokhim, Imam Fadhkur; Rahmatullah, Asfani; Faqih, Fauziah Nur; Ifada, Noor (Jurnal Informatika: Jurnal Pengembangan IT, 2025)
During the pandemic, the COVID-19 virus spread very quickly through the air so that the government implemented a social distancing policy. However, the high number of patients in the therapy waiting room of Syarifah Ambami Rato Ebu Bangkalan Hospital is feared to make the policy not run optimally. The purpose of this study is to create an online therapy queue system abbreviated as SMART in order to reduce crowds in hospitals. In developing SMART, the Waterfall method is used so that it is sequential starting from system needs analysis, design, to implementation and maintenance. The results of functional testing show that all application features can run well. Furthermore, the usability evaluation using the System Usability Scale (SUS) method produced a score of 70, which indicates that the system has a good level of acceptability and usability. Other values obtained in the Acceptability Ranges are Marginal, the Grades Scale value is C, the Adjective value is Good, and the Promoters and Detractors value is Passive. The implementation of this SMART system has the potential to increase the operational effectiveness of hospitals in managing patient flow and significantly improve user experience through usability evaluation.